2021
DOI: 10.1002/1873-3468.14196
|View full text |Cite
|
Sign up to set email alerts
|

CircRNAs in gastric cancer: current research and potential clinical implications

Abstract: Gastric cancer (GC) has a dismal prognosis and is also one of the most commonly diagnosed malignancies worldwide. circRNAs are covalently closed circular RNA molecules without 5′‐cap and a 3′‐tail, currently listed among the broad noncoding RNA family. circRNAs participate in a variety of pathophysiological processes relevant to human diseases, especially malignancies, including GC. Compelling evidence has shown that circRNAs can function by sponging miRNAs, interacting with RNA binding proteins, and encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Accordingly, circRNAs have attracted more attention in tumor pathogenesis and biomarker research in recent years. In the field of GC, a number of abnormally expressed circRNAs have been discovered, and their functions and molecular mechanisms have been revealed 13,21 . For example, Yu et al 22 reported that circ‐TNPO3 acts as a protein decoy for IGF2BP3 to regulate the MYC‐SNAIL axis suppressing the proliferation and metastasis of GC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, circRNAs have attracted more attention in tumor pathogenesis and biomarker research in recent years. In the field of GC, a number of abnormally expressed circRNAs have been discovered, and their functions and molecular mechanisms have been revealed 13,21 . For example, Yu et al 22 reported that circ‐TNPO3 acts as a protein decoy for IGF2BP3 to regulate the MYC‐SNAIL axis suppressing the proliferation and metastasis of GC.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of GC, a number of abnormally expressed circRNAs have been discovered, and their functions and molecular mechanisms have been revealed. 13 , 21 For example, Yu et al 22 reported that circ‐TNPO3 acts as a protein decoy for IGF2BP3 to regulate the MYC‐SNAIL axis suppressing the proliferation and metastasis of GC. Zhang et al 23 identified that circLARP4 could be an miR‐424‐5p sponge and regulate large tumor suppressor kinase 1 (LATS1) expression to affect cell proliferation and invasion of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the detection of circRNAs in tumors is mainly focused on tissue samples, which are more invasive and not suitable for early clinical tumor diagnosis ( Zhou Q. et al, 2021 ; Lu et al, 2021 ; Shen et al, 2021 ) compared to other clinical samples such as serum, urine, and body fluids. CircRNAs are potential novel tumor biomarkers due to their high stability, conservatism, prevalence, tissue, and disease specificity ( Ali et al, 2021 ; Tian et al, 2021 ; Vakhshiteh et al, 2021 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Additionally, non-coding RNAs, including circular RNAs, long non-coding RNAs (lncRNAs), and microRNAs (miRNAs), play critical roles in modulating GC [ 115 , 116 , 117 , 118 ]. Hsa_circ_0017639, a circular RNA, is increased in GC cell lines and promotes proliferation and migration by increasing USP3 expression by sponging miR-224-5p [ 23 ].…”
Section: Usps and Gcmentioning
confidence: 99%